2018
DOI: 10.1186/s12890-018-0685-6
|View full text |Cite
|
Sign up to set email alerts
|

Relative lymphocyte count as an indicator of 3-year mortality in elderly people with severe COPD

Abstract: BackgroundPrognostic stratification of elderly patients with chronic obstructive pulmonary disease (COPD) is difficult due to the wide inter-individual variability in the course of the disease. No marker can exactly stratify the evolution and natural history of COPD patients. Studies have shown that leukocyte count is associated with increased risk of mortality in COPD patients. The aim of this study was to evaluate the possible role of relative lymphocyte count as a risk marker for mortality in elderly patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 37 publications
2
28
1
Order By: Relevance
“…The study showed that relative lymphocyte count ≤ 20% were signi cantly associated with higher risk of death in elderly patients with moderate-to-severe COPD. [15] Xiong et al and Yao et al found that patients with COPD who died had lower lymphocyte count than patients who survived, but lymphocyte count was not an independent risk factor for in-hospital mortality of AECOPD patients. [16,17] We observed that lymphocytopenia occurred in more than 65% of patients in non-survivors group and also an independent risk factor for in-hospital mortality (OR 3.60 (1.10-11.76)).…”
Section: Discussionmentioning
confidence: 96%
“…The study showed that relative lymphocyte count ≤ 20% were signi cantly associated with higher risk of death in elderly patients with moderate-to-severe COPD. [15] Xiong et al and Yao et al found that patients with COPD who died had lower lymphocyte count than patients who survived, but lymphocyte count was not an independent risk factor for in-hospital mortality of AECOPD patients. [16,17] We observed that lymphocytopenia occurred in more than 65% of patients in non-survivors group and also an independent risk factor for in-hospital mortality (OR 3.60 (1.10-11.76)).…”
Section: Discussionmentioning
confidence: 96%
“…A low relative lymphocyte count is associated with a high mortality rate in elderly patients with severe COPD [21]. A characteristic cellular immune response with important diagnostic signi cance in the airway and lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Low lymphocyte count is a physiological adaptation mechanism of the immune system to increasing age. 18 Additively, lymphocyte count is expected to decrease at high altitude. 19 Eosinophilia in patients living at low altitude may be attributed to better response to steroid treatment and greater number in the early stage.…”
Section: Discussionmentioning
confidence: 99%